Range of motion deficits in professional tennis players - Vad, V.; Altchek, D. W. (2001)
We prospectively evaluated one hundred professional men's tour (mean age 25.4 years) tennis players. Range-of-motion studies were done on the dominant and non-dominant upper extremities for the shoulder as well as for the lead and non-lead hip for the lower extremities as well as lumbar spinal flexion. The players were divided into two groups for the low back and two groups for the shoulder. If players had a history of low back symptoms for more than two weeks limiting tennis performance, they were considered to be in the symptomatic low back group. If this was not the case, they were in the asymptomatic low back group. Similarly there were two groups for the shoulder. All measurements were done by one observer. The incidence of low back pain was 40% whereas the incidence of shoulder pain was 44%. In the symptomatic shoulder group there was a 15.2 degree deficit in the dominant shoulder when compared to the non-dominant shoulder at 90 degrees abduction in internal rotation. For cross-chest adduction the difference was 7.2 cm. For the asymptomatic shoulder group there was a 7.5 degree difference between the dominant and non-dominant extremity at 90 degrees abduction in internal rotation. For cross-chest adduction the difference was 2.3 cm. The symptomatic shoulder group had significantly more differences compared to the asymptomatic shoulder group when comparing the dominant to non-dominant upper extremity in 90 degrees abduction with internal rotation and in cross-chest adduction (p<0.05). The 10% error rate using standard goniometric measurements were taken into consideration. In the symptomatic low back group, there was a 7.6 degree deficit in hip internal rotation in the lead hip when compared to the non-lead hip whereas there was 3.2 degree difference for the asymptomatic group (p<0.05). In the symptomatic low back group, the difference in distance in centimetres for PABERE's manoeuvre (distance measured from the knee to the floor) was 8.2 cm when comparing the lead hip to the non-lead hip compared to a difference of 3.2 cm in the asymptomatic group (p<0.05). Based on above findings we conclude that excessive internal rotation deficits in the dominant shoulder as well as in the lead hip compared to the non-dominant shoulder and the non-lead hip respectively are highly correlated with presence of shoulder and low back pain respectively. We therefore recommend shoulder as well as hip internal rotation stretching programs and shoulder cross-chest adduction stretches to minimise the incidence of shoulder and low back pain on the men' s tennis tour.